A Cumulative Approach towards Fixing Constraints of an Organizational Output as per Concluding Break Even Point by Simulink Model - Aswal, Pankaj; Kumar, Manish; Singh, Suyash Kumar (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969129);" role="presentation">A strategy <span dir="ltr" style="left: calc(var(--scale-factor)*120.02px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945197);" role="presentation">(business or marketing) <span dir="ltr" style="left: calc(var(--scale-factor)*223.37px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902513);" role="presentation">that <span dir="ltr" style="left: calc(var(--scale-factor)*243.05px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942734);" role="presentation">integrates an organization's marketin<span dir="ltr" style="left: calc(var(--scale-factor)*396.43px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01113);" role="presentation">g goals into a <span dir="ltr" style="left: calc(var(--scale-factor)*461.14px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930927);" role="presentation">whole <span dir="ltr" style="left: calc(var(--scale-factor)*490.06px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.872445);" role="presentation">segment <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932588);" role="presentation">internal <span dir="ltr" style="left: calc(var(--scale-factor)*106.10px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930368);" role="presentation">(organizational) and external <span dir="ltr" style="left: calc(var(--scale-factor)*227.33px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957163);" role="presentation">(competitive) level<span dir="ltr" style="left: calc(var(--scale-factor)*304.27px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.991281);" role="presentation">, ideally <span dir="ltr" style="left: calc(var(--scale-factor)*341.23px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921107);" role="presentation">drawn <span dir="ltr" style="left: calc(var(--scale-factor)*369.91px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924558);" role="presentation">from market research, <span dir="ltr" style="left: calc(var(--scale-factor)*463.78px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.864449);" role="presentation">emphasizes <span dir="ltr" style="left: calc(var(--scale-factor)*513.46px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904332);" role="presentation">on <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955824);" role="presentation">the ideal product mix to a<span dir="ltr" style="left: calc(var(--scale-factor)*178.61px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953481);" role="presentation">chieve maximum profit potential. <span dir="ltr" style="left: calc(var(--scale-factor)*318.31px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972737);" role="presentation">In the following res<span dir="ltr" style="left: calc(var(--scale-factor)*399.19px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911696);" role="presentation">earch article author emphasize <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947558);" role="presentation">on various types of non-<span dir="ltr" style="left: calc(var(--scale-factor)*173.06px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975976);" role="presentation">linearity <span dir="ltr" style="left: calc(var(--scale-factor)*209.93px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915372);" role="presentation">associated with product development phase <span dir="ltr" style="left: calc(var(--scale-factor)*391.15px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.05521);" role="presentation">to l<span dir="ltr" style="left: calc(var(--scale-factor)*405.19px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948838);" role="presentation">ose control on its production <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916242);" role="presentation">output. <span dir="ltr" style="left: calc(var(--scale-factor)*103.10px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949035);" role="presentation">It is usually a bundle of tangible and intangible <span dir="ltr" style="left: calc(var(--scale-factor)*299.95px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94007);" role="presentation">value of attributes which decides the role of marketing r<span dir="ltr" style="left: calc(var(--scale-factor)*75.38px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898635);" role="presentation">egarding <span dir="ltr" style="left: calc(var(--scale-factor)*114.02px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892924);" role="presentation">benef<span dir="ltr" style="left: calc(var(--scale-factor)*136.22px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93603);" role="presentation">its, features, functions and its usage <span dir="ltr" style="left: calc(var(--scale-factor)*289.01px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.979198);" role="presentation">that a seller offers to a buyer for <span dir="ltr" style="left: calc(var(--scale-factor)*430.66px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924453);" role="presentation">purchase, the optimize <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937187);" role="presentation">value is calculated by applying non-<span dir="ltr" style="left: calc(var(--scale-factor)*219.77px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946386);" role="presentation">linear mathematical genetic algorithm function with interaction of variable <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962536);" role="presentation">(A) and (B). <span dir="ltr" style="left: calc(var(--scale-factor)*124.22px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926185);" role="presentation">The main objective <span dir="ltr" style="left: calc(var(--scale-factor)*204.53px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926269);" role="presentation">is to study <span dir="ltr" style="left: calc(var(--scale-factor)*248.69px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885579);" role="presentation">the breakeven <span dir="ltr" style="left: calc(var(--scale-factor)*307.39px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914896);" role="presentation">analysis by setting a second order transfer function of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913282);" role="presentation">output of given organization here author wants to calculate the output transfer <span dir="ltr" style="left: calc(var(--scale-factor)*387.19px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953465);" role="presentation">function <span dir="ltr" style="left: calc(var(--scale-factor)*423.10px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928948);" role="presentation">of an organization with a <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934485);" role="presentation">set of given input variables (it may be quantity of raw <span dir="ltr" style="left: calc(var(--scale-factor)*291.77px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895261);" role="presentation">mat<span dir="ltr" style="left: calc(var(--scale-factor)*306.67px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930757);" role="presentation">erial, time, money <span dir="ltr" style="left: calc(var(--scale-factor)*382.63px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90045);" role="presentation">etc) various constraints decides the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*454.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948075);" role="presentation">output of any organization. <span dir="ltr" style="left: calc(var(--scale-factor)*187.13px); top: calc(var(--scale-factor)*454.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967039);" role="presentation">The following paper incorporates with concluding product mix with non-<span dir="ltr" style="left: calc(var(--scale-factor)*490.18px); top: calc(var(--scale-factor)*454.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972493);" role="presentation">linearity <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*467.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975298);" role="presentation">error inside the organization and its effect outside variable. <span dir="ltr" style="left: calc(var(--scale-factor)*328.27px); top: calc(var(--scale-factor)*467.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.989315);" role="presentation">The calculation of output var<span dir="ltr" style="left: calc(var(--scale-factor)*452.26px); top: calc(var(--scale-factor)*467.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01229);" role="presentation">iable in terms of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*481.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912109);" role="presentation">contribution has been made by applying simulation an<span dir="ltr" style="left: calc(var(--scale-factor)*288.89px); top: calc(var(--scale-factor)*481.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942114);" role="presentation">d tool of simulation is Matlab